Penguatan Kapasitas Aparatur Desa dalam Perencanaan Keuangan Desa di Desa Guluk-Guluk Kecamatan Guluk-Guluk Kabupaten Sumenep - Mohammad Herli; Hafidhah Hafidhah; Liyanto Liyanto; Miftahol Arifin (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Significantly, Law No. 06 of 2014 concerning the village impacts development in the village. This program aims to provide understanding to village officials in the preparation of the village budget. This stage is crucial so that the direction of village development is structured and follows village conditions. The implementation method includes training and mentoring in making village financial planning, including the Village RPJMD, RKPdesa, and APBDesa. Thus, it is hoped that they can carry out financial management well and achieve accountability in village financial reporting. The implementation of this PkM activity was carried out in Guluk-Guluk Village, Guluk-Guluk District, Sumenep Regency. The activity results show that village officials have increased their ability and understanding of making village financial planning. The involvement of various parties in making village financial planning documents in Guluk-Guluk Village makes the direction of village development directed and follows the village community's expectations. In addition, based on the questionnaire results, it can be concluded that village officials have improved their understanding of village financial planning.